2021
DOI: 10.1155/2021/8840545
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis of Gasifier Lock Bucket Valve System Based on DBN Method

Abstract: In order to solve the problem of zero-failure data and dynamic failure in gasification system, a dynamic Bayesian network (DBN) combined with Monte Carlo simulations is proposed to analyze the reliability of the gasifier lock bucket valve system. On the basis of studying the structure of the gasifier lock bucket valve system, the reliability model of the system is built based on DBN, and the structure learning is realized. The Monte Carlo simulation is used for the timed ending test in Bayesian estimation, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Te primary goal of this part is to simulate the time-lag correlation between two time series I(i, t) and I(j, t)(i ≠ j) using dynamic Bayesian network (DBN) to realize epidemic STTP network structure learning. Bayesian network is a probabilistic graph model, which represents a group of random variables and their conditional dependencies through a directed acyclic graph (DAG) [25]. Formally, Bayesian networks use nodes to represent random variables (whose probability is Bayesian probability).…”
Section: Epidemic Spatial-temporal Transmission Path (Sttp)mentioning
confidence: 99%
“…Te primary goal of this part is to simulate the time-lag correlation between two time series I(i, t) and I(j, t)(i ≠ j) using dynamic Bayesian network (DBN) to realize epidemic STTP network structure learning. Bayesian network is a probabilistic graph model, which represents a group of random variables and their conditional dependencies through a directed acyclic graph (DAG) [25]. Formally, Bayesian networks use nodes to represent random variables (whose probability is Bayesian probability).…”
Section: Epidemic Spatial-temporal Transmission Path (Sttp)mentioning
confidence: 99%
“…The training process was divided into pre-training and fine-tuning. The pre-training trains all RBMs in an unsupervised manner, whereas fine-tuning is used to fine-tune the weight and bias parameters of the pre-trained model through the implementation of the BP algorithm [31,32]. (…”
Section: Dbn Theorymentioning
confidence: 99%
“…The dynamic Bayesian network (DBN) structure model can effectively represent the structural relationship between node variables in the dynamic risk assessment system of the coal chemical industry and can also calculate the exact value of risk, so its use as the main research method for the dynamic risk assessment of the coal gasification process is suitable. Based on DBN, Liu [ 22 ] conducted a dynamic risk assessment of the changes in the reliability of a gasifier burner system during the operating cycle. The dynamic reliability of the system was inferred from prior data; it was found that the dynamic reliability of the system and its subsystems gradually decreased with an increase in operating time, and the weak links of the system were successfully identified.…”
Section: Introductionmentioning
confidence: 99%